EFEKTIVITAS INFUSA LEMPUYANG GAJAH (Zingiber zerumbet) SEBAGAI ANTIDIARE PADA MENCIT (Mus musculus) - Mustika, Aulia Andi (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2024)
Lempuyang gajah (Zingiber zerumbet) rhizomes have long been consumed as food and treatment of diseases in humans. Lempuyang gajah rhizomes have potential as antidiarrheal that is cheap and easy to find, but there has been no research related to the benefits of lempuyang gajah rhizomes as antidiarrheal. The purpose of this study is to determine the effectivity of lempuyang gajah infusion as an antidiarrheal and the concentration that has the most effective antidiarrheal effect with intestinal protection method. This research also determine the content of secondary metabolites in lempuyang gajah through phytochemical tests. This study used 30 mices divided into five groups consisting of negative control group (Tween 80 [1%]), a positive control group (loperamid HCl suspension), and three groups of treatment with a lempuyang gajah infusion concentration of 25%, 50%, and 100% given orally. The parameters observed were the frequency of defecation, the consistency of faeces, and the duration of diarrhea. The conclusion of this research shows that lempuyang gajah infusion has antidiarrheal effect, lempuyang gajah infusion at a concentration of 50% showed the most effective antidiarrheal effect. Phytochemical test results show lempuyang gajah contains alkaloids and saponins